ASSOCIATION BETWEEN ORTHOREXIA NERVOSA TENDENCY, EATING ATTITUDES AND ANXIETY STUDIED AMONG MEDICAL STUDENTS OF RAWALPINDI MEDICAL UNIVERSITY: A CROSS-SECTIONAL STUDY - Asim, Mehak; Azhar, Saira; Rafique, Momina; Omar, Manaam; Hamid, Sidra (Journal of Pakistan Psychiatric Society, 2025)
OBJECTIVE To assess how prevalent Orthorexia Nervosa is among students at the Rawalpindi Medical University and to explore its relationship with dietary attitudes and anxiety. STUDY DESIGN Descriptive cross-sectional study PLACE AND DURATION OF STUDY This study was conducted at the Rawalpindi Medical University, Pakistan from April to October 2023. METHOD Two hundred and eighty three 283 medical students were assessed using a questionnaire which incorporated items from three standardized tools: ORTO-15 (Orthorexia Nervosa assessment), Hamilton Anxiety Rating Scale (HAM-A), and Eating Attitude Test (EAT-26). The completed questionnaires were collected and analysed. RESULTS The research revealed that a majority, 62.9% of the medical students exhibited signs of Orthorexia Nervosa. However, analyses did not show significant association between the levels of Orthorexia Nervosa with either eating behaviours or anxiety levels. CONCLUSION The study concludes that there is no significant relationship between the tendencies towards Orthorexia Nervosa and dietary behaviours or anxiety levels. Additional research is required to identify potential risk factors associated with orthorexia nervosa.